The challenge of teaching Spanish L1 as pluricentric language from a critical linguistic perspective - López García, María (Borealis – An International Journal of Hispanic Linguistics, 2024)
The aim of this article is to outline an overview and to discuss some constraining factors related to teaching Spanish as L1 in the context of linguistic diversity in Argentina. The underlying argument of this paper is that diverse school materials and teaching methodology involved in teaching Spanish as L1 neglects linguistic diversity. Instead, they subscribe to discourses that reinforce a pyramidal normative structure where the Spanish Royal Academy is the apex, and therefore, so is its linguistic authority. Our suggestion in this regard is that the diversity of voices must have a space not only in the classroom and materials, but also in research processes and academia´s knowledge management. For this purpose, and framed within a glotopolitical approach, this paper analyzes, firstly, the obstacle represented by the fixed categories included in school curriculum such as “language”, “variety”, “standard”, and even “national language”; secondly, the paper reviews the role played by grammatization instruments (such as dictionaries and school textbooks, among others) and their monologic discursive wording. Finally, the article suggests didactic strategies to analyze linguistic varieties in class, and to reinforce a critical reading of norm distribution instruments.